RADIKALISME AGAMA DALAM KONTEKS INDONESIA YANG AGAMIS DAN BERPANCASILA - Agustinus Wisnu Dewantara (Lembaga Penelitian STKIP Widya Yuwana, 2019)
The reality of religious radicalism in Indonesia is increasingly troubling every day, especially after reform. Religious radicalism is displayed in heartbreaking (inhuman) acts of dishonesty, such as the Bali Bombing, Poso tragedy, Ambon, Sambas, Tolikara, etc. All that is evil, such as the act of killing, terrorizing, burning, destroying fellow humans is strangely framed in the name of religion. This paper wants to limit itself to discussing religious radicalism in Indonesia from a philosophical and theological point of view. The method used is the verstehen method by listening to the reality of radicalism and looking at it in the eyes of philosophy. This becomes important for the growth of a good attitude in objectively viewing religions and living them properly in the context of a multicultural and Pancasila Indonesia. Religious theology, education and lectures should be education of peace, humanist aspects of growth, human culture bloomers, and not education about mastering religious materials that are very formal. Religious education must be in harmony with the values of the nation's called Pancasila.